A high-strength sodium alginate-starch composite emulsion gel, a preparation method and application thereof

CN122642534APending Publication Date: 2026-08-28OCEAN UNIV OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611111621.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

[0007]本发明要解决的技术问题是现有的海藻酸钠基乳液凝胶在实际应用中凝胶强度不足、植物油包埋不稳定、交联工艺可控性差,急需开发一种凝胶强度高、油脂包埋稳定、且工艺可控的海藻酸钠基乳液凝胶制备方法

Benefits of technology

(1)凝胶强度显著提升:通过预冻固定化结合低温慢速交联工艺,钙离子扩散速率减缓,与海藻酸钠G嵌段的交联更均匀、更完全,凝胶内部结构致密,凝胶硬度相比传统常温快速交联工艺提升3倍以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122642534A_ABST
    Figure CN122642534A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of functional food materials and bio-based composite material preparation, and in particular to a high-strength sodium alginate-starch composite emulsion gel, a preparation method and application thereof. First, gelatinized starch is homogenized with sucrose fatty acid ester and vegetable oil to prepare a starch composite emulsion, and a stable emulsion system is formed by short straight-chain starch in the starch composite emulsion and vegetable oil; then the emulsion is mixed with a sodium alginate solution, and a calcium alginate network and a starch-oil composite enhanced double-network structure are constructed through pre-freezing immobilization treatment combined with a low-temperature slow calcium ion crosslinking process, thereby solving the problems of weak strength of existing sodium alginate-based emulsion gels, unstable oil and fat embedding, and difficulty in meeting complex food processing conditions, and providing an ideal animal fat replacement material for the development of healthy meat products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional food materials and bio-based composite material preparation technology, specifically to a high-strength sodium alginate-starch composite emulsion gel, its preparation method, and its application. Background Technology

[0002] With increasing consumer health awareness, replacing animal fat in processed meat products has become an important research direction in the food industry. While animal fat imparts excellent flavor, texture, and quality to meat products, it is rich in saturated fatty acids and cholesterol, and excessive intake is closely related to cardiovascular disease, obesity, and other health problems. Vegetable oils, rich in unsaturated fatty acids, are an ideal source of animal fat substitutes. However, vegetable oils are liquid at room temperature, and directly replacing animal fat with them can lead to problems such as loose texture, oil seepage, and poor taste in meat products. Therefore, structuring vegetable oils into emulsion gels to give them solid properties and mechanical strength similar to animal fats has become a key technological path to achieving a healthy alternative.

[0003] Sodium alginate, as a natural polysaccharide, is widely used in the food gel industry due to its good biocompatibility, non-toxicity, and mild ionic cross-linking properties. In aqueous solution, the guluronic acid (G) blocks on the sodium alginate molecular chain can specifically coordinate with calcium ions to form a stable three-dimensional network structure, which can be used as a gel matrix for encapsulating vegetable oils. For example, Chinese patent CN109601873A, "Preparation Method of Sodium Alginate Gel Slow-Release Pork Backfat Substitute and Its Application in Fermented Sausage," discloses the use of sodium alginate-calcium salt composite agent to prepare a gel-like fat substitute, replacing part of the pork backfat used in traditional sausages; Chinese patent CN109619537A, "Preparation of Fat Substitute and Its Application in Meatballs," discloses that the fat substitute includes sodium alginate, calcium sulfate dihydrate, glucono-δ-lactone, propylene glycol alginate, maltodextrin, fucoidan, and fucoxanthin as base materials. However, sodium alginate-based emulsion gels face the following problems in practical applications: Insufficient gel strength: Pure sodium alginate gel mainly relies on ionic bonds to maintain its network structure. Its mechanical strength and toughness are limited, making it difficult to maintain structural integrity during food processing (such as chopping, filling, and sterilization). This can easily lead to oil leakage and gel breakage.

[0004] Unstable encapsulation of vegetable oils: Sodium alginate has a weak ability to encapsulate hydrophobic vegetable oils. The gel network formed by traditional cross-linking methods has large pores, which makes it difficult to effectively bind oil droplets, resulting in the gradual precipitation of oils during storage or processing.

[0005] Poor controllability of crosslinking process: Traditional calcium ion crosslinking is mostly carried out rapidly at room temperature. The calcium ion diffusion rate is too fast, resulting in excessive crosslinking on the gel surface and insufficient crosslinking inside, forming a structural defect of "strong outside and weak inside", which further reduces the overall strength and stability of the gel.

[0006] Therefore, developing a method for preparing sodium alginate-based emulsion gels with high gel strength, stable oil encapsulation, and controllable process is of great practical significance for promoting the application of vegetable oils in meat products as a substitute for animal fats. Summary of the Invention

[0007] The technical problem to be solved by this invention is that existing sodium alginate-based emulsion gels have insufficient gel strength, unstable vegetable oil encapsulation, and poor controllability of crosslinking processes in practical applications. There is an urgent need to develop a method for preparing sodium alginate-based emulsion gels with high gel strength, stable oil encapsulation, and controllable process.

[0008] To address the problems of existing technologies, this invention provides a method for preparing a high-gel-strength sodium alginate-starch composite emulsion gel. The method first homogenizes gelatinized corn starch with sucrose fatty acid esters and vegetable oil to prepare a starch composite emulsion, utilizing the short-chain amylose in the starch composite emulsion to form a stable emulsion system with the vegetable oil. Then, this emulsion is mixed with a sodium alginate solution, and through pre-freezing immobilization combined with a low-temperature slow calcium ion crosslinking process, a dual-network structure reinforced by a calcium alginate network and a starch-oil composite is constructed. This solves the problems of weak gel strength, unstable oil encapsulation, and difficulty in meeting the complex conditions of food processing in existing sodium alginate-based emulsion gels, providing an ideal animal fat substitute for the development of healthy meat products. The resulting product can be used as an animal fat substitute in processed foods such as ham sausages and minced meat products, and can also be used in functional oil delivery and nutritional supplements.

[0009] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a high-strength sodium alginate-starch composite emulsion gel, comprising the following steps: (1) Preparation of sodium alginate solution: Disperse sodium alginate powder in water and fully hydrate and dissolve to obtain sodium alginate solution; (2) Preparation of starch gelatinized liquid: Starch (selected from one or more of corn starch, potato starch, cassava starch, wheat starch, pea starch, rice starch and food-grade modified starch, preferably corn starch. More preferably, the corn starch is food-grade ordinary corn starch or high amylose corn starch, and its amylose content is preferably 15% to 35% to facilitate the formation of a starch network with certain chain segment entanglement and oil complexation ability after gelatinization) is dispersed in water to prepare a suspension with a mass concentration of 1.0% to 8.0%. After gelatinization treatment, the starch particles are broken down and short amylose is released to obtain starch gelatinized liquid. The mass concentration of starch gelatinized liquid is controlled at 1.0% to 8.0% to ensure that the system has good fluidity and homogenizability while providing sufficient starch molecular chains for oil droplet stabilization and gel network enhancement. When the starch concentration is below 1.0%, the system viscosity and physical filling effect are insufficient, and oil droplets are prone to coalescence or precipitation; when the starch concentration is above 8.0%, the viscosity of the gelatinized liquid is too high, which easily leads to problems such as uneven gelatinization, difficulty in homogenization and difficulty in removing air bubbles, which is not conducive to the formation of a uniform emulsion gel. (3) Preparation of starch composite emulsion: Sucrose fatty acid esters are added to the starch gelatinized liquid as emulsifiers. The amount of sucrose fatty acid esters added is 0.5-3.0% of the mass of the starch gelatinized liquid. When the amount added is less than 0.5%, the oil droplet surface is not covered enough, and the emulsion is prone to aggregation and stratification. When the amount added is more than 3.0%, the excessive emulsifier may adversely affect the flavor, cost and subsequent gel structure of the system. Then, vegetable oil is added. The mass ratio of vegetable oil to corn starch is 1:1 to 5:1. When the ratio is less than 1:1, the vegetable oil content is too low, and the fat simulation effect as a substitute for animal fat is insufficient. When the ratio is more than 5:1, there is too much oil phase that can be stabilized by a unit of starch, and the oil droplets are prone to aggregation or precipitation, which may weaken the continuity of the subsequent calcium alginate gel network. Then, homogenization is performed to make the vegetable oil uniformly dispersed in the starch gelatinized liquid to form a stable starch composite emulsion. (4) Pre-freezing blending: Sodium alginate solution and starch composite emulsion are mixed at a volume ratio of 1:1 to 3:1. When the proportion of starch composite emulsion is too high, the continuous sodium alginate phase is insufficient, the overall strength of the gel decreases after cross-linking, and the risk of oil exudation increases. When the proportion of sodium alginate solution is too high, although the gel strength can be improved, the oil loading decreases and the fat substitution effect weakens. Stir thoroughly and perform degassing treatment to eliminate the air bubbles introduced during the mixing process to obtain a composite gel solution. (5) Pre-freezing and immobilization treatment: The composite gel solution is filled into a mold (the inner cavity shape can be customized as needed, including but not limited to spheres, cubes, cylinders, stars, hearts, etc.), and placed at -20~-80℃ for pre-freezing treatment for 2~12 hours to allow the gel system to form a stable frozen block structure; the pre-freezing temperature is controlled at -20℃~-80℃, which can enable the composite gel solution to quickly form a stable frozen block, avoid oil droplets from floating, agglomerating or delaminating before crosslinking, and keep the sample in the preset shape during demolding and transfer. When the temperature is higher than -20℃, the freezing speed is slower, and the interior may not be frozen sufficiently, affecting the integrity of subsequent molding; when the temperature is lower than -40℃, although the freezing speed is faster, energy consumption increases, and excessively fast freezing may bring greater internal stress and local structural defects. Pre-freezing not only fixes the gel shape but also regulates the microstructure of the gel network through ice crystal formation. During pre-freezing, free water in the system first forms ice crystals, while sodium alginate, gelatinized starch, and emulsified oil droplets are displaced and concentrated in the unfrozen phase, thereby increasing the local polymer concentration. The ice crystals act as temporary templates; during subsequent low-temperature crosslinking and thawing, their locations transform into micropores or water channels, facilitating uniform infiltration of calcium ions from the outside in and reducing the "hard outside, soft inside" phenomenon caused by instantaneous excessive crosslinking. Simultaneously, freezing fixation restricts oil droplet migration and aggregation, ensuring a uniform distribution of oil droplets before crosslinking, ultimately forming a denser and more uniform calcium alginate-starch-oil composite network, laying the foundation for subsequent uniform crosslinking. (6) Low-temperature slow crosslinking: Demold the pre-frozen block and immerse it in a low-temperature calcium chloride solution at 0~4℃, with a mass concentration of 1.0~10.0%; carry out a slow crosslinking reaction for 12~48 hours under low-temperature conditions to allow calcium ions to penetrate uniformly and fully coordinate with the sodium alginate G block; the low-temperature environment significantly slows down the diffusion rate of calcium ions, allowing them to penetrate uniformly into the gel and form a more complete and uniform coordination complex with the sodium alginate G block. During this process, the starch composite emulsion, which was uniformly dispersed in the sodium alginate matrix before pre-freezing, undergoes complexation with calcium ions through its short-chain starch, and at the same time acts as a physical filler and oil stabilizer to further enhance the gel network structure. After crosslinking is completed, remove the gel and rinse the surface with deionized water; (7) Emulsion gel formation: The cross-linked gel is taken out and thawed to obtain a high gel strength sodium alginate-starch composite emulsion gel.

[0010] Furthermore, in step (1), the mass concentration of the sodium alginate solution is 1.0~4.0%; the solution is left to stand for 12~24 hours to ensure that the sodium alginate is fully hydrated and dissolved and to eliminate air bubbles in the solution, and then it is ready for use.

[0011] Furthermore, step (2) gelatinization is performed using microwave treatment. Microwave gelatinization has the advantages of rapid heating, high heat transfer efficiency, and short processing time. Microwaves can cause starch granules to rapidly absorb water and swell, destroying their crystal structure and releasing starch molecular chains, thereby forming a gelatinized liquid with suitable viscosity and uniform dispersion. The specific steps are as follows: place the suspension in a microwave device, set the microwave power to 400~800 W, and the radiation heating time to 30~90 seconds to fully gelatinize the starch granules and release short-chain starch. Lower power combined with a longer time is conducive to gentle gelatinization, while higher power combined with a shorter time is conducive to rapid gelatinization. This parameter range is suitable for the gelatinization treatment of starch suspensions of different concentrations. After the treatment is completed, allow it to cool naturally to room temperature (20~25℃) to obtain a uniform starch gelatinized liquid.

[0012] Furthermore, the homogenization method in step (3) is to use a high-speed homogenizer for homogenization, with a homogenization speed of 8000~15000 rpm and a homogenization time of 3~10 minutes. These parameters can provide sufficient shear force to disperse the vegetable oil into smaller oil droplets in the starch gelatinization liquid and to allow sucrose fatty acid esters to be quickly adsorbed at the oil-water interface, thereby forming a stable emulsion.

[0013] Furthermore, the vegetable oil mentioned in step (3) includes, but is not limited to, one or more of soybean oil, rapeseed oil, peanut oil, sunflower oil, and corn oil.

[0014] The high-strength sodium alginate-starch composite emulsion gel prepared by the above method exhibits a gel hardness more than three times higher than that obtained by traditional room-temperature rapid cross-linking processes. Its size and shape are controllable, and its hardness ranges from 800 to 1000 g (e.g., ...). Figure 4 (As shown).

[0015] The above-mentioned high-strength sodium alginate-starch composite emulsion gel is used as an animal fat substitute in processed foods.

[0016] The beneficial effects of this invention are as follows: (1) Significantly improved gel strength: By combining pre-freezing immobilization with low-temperature slow cross-linking process, the calcium ion diffusion rate is slowed down, and the cross-linking with sodium alginate G block is more uniform and complete. The internal structure of the gel is dense, and the gel hardness is more than 3 times higher than that of the traditional room temperature fast cross-linking process.

[0017] (2) Enhanced oil encapsulation stability: Using starch composite emulsion technology, vegetable oil is pre-emulsified and stabilized in a gelatinized starch system, and then blended and cross-linked with sodium alginate to form a highly dispersed and stably encapsulated double-network emulsion gel structure, significantly reducing oil leakage. (e.g.) Figure 5 (As shown).

[0018] (3) Dual-network synergistic enhancement: The calcium alginate network and the starch-oil composite network form a dual-enhancing structure, which retains the ionic cross-linking characteristics of sodium alginate and gives full play to the physical filling and emulsifying stabilizing effect of starch, thereby achieving higher gel strength while reducing the amount of sodium alginate used.

[0019] (4) The process is controllable and widely applicable: Pre-freezing combined with mold molding can achieve precise control of gel shape and size; the low-temperature crosslinking process parameters are highly controllable and easy to scale up from laboratory to industrial production.

[0020] (5) High safety and broad application prospects: All raw materials are food-grade and no toxic or harmful chemical reagents are introduced. The resulting emulsion gel can be directly used as a substitute for animal fat in processed foods such as ham sausage and minced meat products, which helps to reduce the intake of saturated fatty acids and cholesterol and improve the nutritional and health value of food. Attached Figure Description

[0021] Figure 1 Comparison of gels prepared by traditional titration (first from left) and low-temperature slow cross-linking gels of different sizes (second to fifth from left).

[0022] Figure 2 Images of gels of different shapes and sizes prepared after pre-freezing and immobilization.

[0023] Figure 3 A comparison of the appearance of pork fat blocks (top image) and emulsion gel (bottom image) (left image) and their application in sausages (right image).

[0024] Figure 4 A comparison of the hardness of gels prepared by traditional titration and pre-frozen immobilized gels.

[0025] Figure 5 A comparison of the oil exudation rate of gels prepared by traditional titration and pre-frozen immobilized gels under the same extrusion force.

[0026] Figure 6 The size and morphology of gels formed under different pre-freezing temperatures were determined.

[0027] Figure 7 The size and morphology of gels formed under different crosslinking time conditions were determined. Detailed Implementation

[0028] The following description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

[0029] The following embodiments can be understood as illustrating a part of the structure or method of the present invention individually, or as combining embodiments to explain the broader structure or method of the present invention. Unless otherwise specified, the instruments, reagents, materials, etc., involved in the following embodiments are all conventional instruments, reagents, materials, etc., already existing in the prior art and obtainable through legitimate commercial channels. Unless otherwise specified, the experimental methods, detection methods, etc., involved in the following embodiments are all conventional experimental methods, detection methods, etc., already existing in the prior art.

[0030] Parameter optimization: Using gel formation integrity, hardness, oil retention, and ease of handling as evaluation indicators, single-factor optimization was performed on pre-freezing temperature, pre-freezing time, cross-linking temperature, cross-linking time, and microwave gelatinization parameters. For example... Figure 6 The results show that when the pre-freezing temperature is too high, the sample is not fully frozen and is prone to deformation during demolding and cross-linking; when the pre-freezing temperature is too low, energy consumption increases and large freezing stress may occur inside the sample. If the pre-freezing time is too short, the center of the frozen block is not completely fixed, while if the pre-freezing time is too long, it is detrimental to production efficiency. Therefore, pre-freezing at -20℃ to -40℃ for 2 to 12 hours can meet the molding requirements.

[0031] like Figure 7 As shown, optimization of low-temperature crosslinking conditions revealed that lower crosslinking temperatures can slow down calcium ion diffusion and instantaneous surface crosslinking, which helps improve the uniformity of crosslinking inside and outside the gel. If the crosslinking time is too short, internal crosslinking is insufficient; if the crosslinking time is too long, the production cycle increases and the increase in gel hardness tends to plateau. Therefore, a low-temperature crosslinking time of 12–48 hours is suitable.

[0032] Example 1: A method for preparing a high-strength sodium alginate-starch composite emulsion gel includes the following steps: (1) Preparation of sodium alginate solution: Weigh 3.0 g of sodium alginate and disperse it in 100 mL of deionized water. Stir well and let stand overnight to obtain a sodium alginate solution with a mass fraction of 3.0%.

[0033] (2) Preparation of starch gelatinization solution: Weigh 4.0 g of corn starch (purchased from Foshan Guonong Starch Co., Ltd., food grade) and disperse it in 100 mL of deionized water, and stir evenly. Place the suspension in a microwave oven, set the power to 600 W, heat for 60 seconds, and take it out and stir once every 20 seconds to prevent clumping. After full gelatinization, cool to room temperature.

[0034] (3) Preparation of starch composite emulsion: Add 1.0 g of sucrose fatty acid ester to the starch gelatinized liquid above, stir to dissolve, then add 12.0 g of soybean oil, and homogenize at 12000 rpm for 5 minutes using a high-speed homogenizer to obtain a stable starch composite emulsion.

[0035] (4) Pre-freezing blending: Mix the above sodium alginate solution and starch composite emulsion at a volume ratio of 1:1, stir evenly, and degas.

[0036] (5) Pre-freezing and immobilization treatment: The mixed adhesive solution is injected into a cylindrical silicone mold and placed at -30℃ for 4 hours to pre-freeze it completely to form a frozen block.

[0037] (6) Low-temperature slow crosslinking: Prepare a 5.0% calcium chloride solution and pre-cool it to the target temperature in a -20℃ refrigerator. Demold the pre-frozen block and immediately immerse it in a 4℃ calcium chloride solution for crosslinking for 24 hours. At the same time, inject the mixed adhesive solution into a 10 mL syringe and drop it at a rate of 2 s / drop from 10 cm above the surface of the calcium chloride solution. Crosslinking occurs after the droplet contacts the water surface, which is the control group prepared by the traditional titration method.

[0038] (7) Emulsion gel formation: Take out the cross-linked gel, thaw it at room temperature, and wash the surface with deionized water to obtain a high gel strength sodium alginate-starch composite emulsion gel.

[0039] Result verification: 1. For example Figure 1 As shown, the gel particles prepared by traditional titration are small in size, and the forming size is limited by the size of the droplet; while the gel prepared by pre-freezing immobilization combined with low-temperature cross-linking can form a larger, complete spherical structure with a fuller appearance and continuous surface. This shows that the method of the present invention breaks through the limitation of traditional titration method, which can only prepare small-particle gels, and can achieve stable forming of larger-sized emulsion gels.

[0040] 2. For example Figure 2 As shown, after pre-freezing and immobilization, the composite gel solution can be used to prepare gels of different shapes such as star, triangle, heart, circle, and flower according to the mold shape. Moreover, it can still maintain good appearance integrity after demolding, indicating that the pre-freezing and immobilization treatment can effectively fix the initial morphology of the gel and improve the designability of the gel shape and size.

[0041] 3. For example Figure 3 As shown, the emulsion gel prepared by this invention has a milky white appearance similar to animal fat blocks and a certain solid state, and can be cut or shaped before being added to the sausage system. The sausage cross-section shows that the emulsion gel can be embedded relatively completely into the minced meat matrix, indicating its feasibility as a substitute for animal fat in processed meat products such as sausages.

[0042] 4. For example Figure 4 As shown, the emulsion gel prepared by the present invention forms a double-network emulsion gel structure with highly dispersed and stably embedded oils, and the oil leakage rate is significantly reduced under the same extrusion conditions.

[0043] Example 2: A method for preparing a high-strength sodium alginate-starch composite emulsion gel includes the following steps: (1) Preparation of sodium alginate solution: Weigh 1.0 g of sodium alginate and disperse it in 100 mL of deionized water. Stir well and let stand overnight to obtain a sodium alginate solution with a mass fraction of 1.0%.

[0044] (2) Preparation of starch gelatinization solution: Weigh 1.0 g of corn starch (purchased from Foshan Guonong Starch Co., Ltd., food grade) and disperse it in 100 mL of deionized water, and stir evenly. Place the suspension in a microwave oven, set the power to 400 W, and heat for 90 seconds. During this period, take it out and stir once every 30 seconds to prevent clumping. After full gelatinization, cool to room temperature.

[0045] (3) Preparation of starch composite emulsion: Add 0.6 g of sucrose fatty acid ester to the starch gelatinized liquid, stir to dissolve, then add 1.0 g of soybean oil, and homogenize at 8000 rpm for 10 minutes using a high-speed homogenizer to obtain a stable starch composite emulsion.

[0046] (4) Pre-freezing blending: Mix the above sodium alginate solution and starch composite emulsion at a volume ratio of 2:1, stir evenly, and degas.

[0047] (5) Pre-freezing and immobilization treatment: The mixed adhesive solution is injected into a cylindrical silicone mold and placed at -20℃ for 12 hours to allow it to solidify completely and form a frozen block.

[0048] (6) Low-temperature slow crosslinking: Prepare a calcium chloride solution with a mass concentration of 1.0% and pre-cool it to the target temperature in a -20℃ refrigerator. Demold the pre-frozen blocks and immediately immerse them in a calcium chloride solution at 4℃ for crosslinking for 48 hours.

[0049] (7) Emulsion gel formation: Take out the cross-linked gel, thaw it at room temperature, and wash the surface with deionized water to obtain a high gel strength sodium alginate-starch composite emulsion gel.

[0050] Example 3: A method for preparing a high-strength sodium alginate-starch composite emulsion gel includes the following steps: (1) Preparation of sodium alginate solution: Weigh 4.0 g of sodium alginate and disperse it in 100 mL of deionized water. Stir well and let stand overnight to obtain a sodium alginate solution with a mass fraction of 4.0%.

[0051] (2) Preparation of starch gelatinization solution: Weigh 8.0 g of corn starch (purchased from Foshan Guonong Starch Co., Ltd., food grade) and disperse it in 100 mL of deionized water, and stir evenly. Place the suspension in a microwave oven, set the power to 800 W, heat for 30 seconds, and take it out and stir once every 10 seconds to prevent clumping. After full gelatinization, cool to room temperature.

[0052] (3) Preparation of starch composite emulsion: Add 3.0 g of sucrose fatty acid ester to the above starch gelatinized liquid, stir to dissolve, then add 40.0 g of soybean oil, and homogenize at 15000 rpm for 3 minutes using a high-speed homogenizer to obtain a stable starch composite emulsion.

[0053] (4) Pre-freezing blending: Mix the above sodium alginate solution and starch composite emulsion at a volume ratio of 3:1, stir evenly, and degas.

[0054] (5) Pre-freezing and immobilization treatment: The mixed adhesive solution is injected into a cylindrical silicone mold and placed at -40℃ for 2 hours to pre-freeze it completely to form a frozen block.

[0055] (6) Low-temperature slow crosslinking: Prepare a calcium chloride solution with a mass concentration of 10.0% and pre-cool it to the target temperature in a -20℃ refrigerator. Demold the pre-frozen blocks and immediately immerse them in a calcium chloride solution at 4℃ for 12 hours for crosslinking.

[0056] (7) Emulsion gel formation: Take out the cross-linked gel, thaw it at room temperature, and wash the surface with deionized water to obtain a high gel strength sodium alginate-starch composite emulsion gel.

[0057] Application Examples: Lean pork was trimmed and minced, then mixed with salt, sugar, spices, and ice water to obtain minced meat. The high-strength sodium alginate-starch composite emulsion gel prepared in Example 1 was granulated and added to the minced meat at a ratio of 30% to 100% of the animal fat mass, replacing pork backfat. The mixture was then continued to mix at a low speed to ensure the emulsion gel was evenly dispersed throughout the minced meat system. The mixed minced meat was then stuffed into sausage casings, degassed, tied, and then heated, cooked, and cooled to obtain sausages containing the emulsion gel fat substitute.

[0058] Result verification: like Figure 4 As shown, the emulsion gel in the obtained sausage can maintain a relatively intact shape and maintain the texture and cross-sectional appearance of the sausage while reducing the amount of animal fat added.

[0059] In summary, this invention addresses the application needs of emulsion gels as animal fat substitutes in processed foods such as ham sausages, and the problem that sodium alginate, as a gelling material, suffers from weak gel strength and difficulty in stably encapsulating vegetable oils, thus failing to meet the complex conditions of food processing. It proposes a preparation strategy combining starch composite emulsion enhancement with low-temperature slow calcium ion crosslinking. The method first involves gelatinizing corn starch, adding sucrose fatty acid esters and vegetable oil, and homogenizing to prepare a starch composite emulsion. Then, this emulsion is mixed with a sodium alginate solution, pre-frozen for immobilization, and then immersed in a low-temperature calcium chloride solution for slow crosslinking. The composite emulsion gel prepared by this invention exhibits more than three times the gel strength compared to traditional calcium ion crosslinking processes, and significantly enhanced stability in encapsulating vegetable oils. It can meet the requirements of various complex processing conditions in food processing, providing an ideal fat substitute for the development of healthy meat products.

[0060] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.

[0061] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.

[0062] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.

Claims

1. A method for preparing a high-strength sodium alginate-starch composite emulsion gel, characterized in that... Includes the following steps: (1) Preparation of sodium alginate solution: Disperse sodium alginate powder in water and fully hydrate and dissolve to obtain sodium alginate solution; (2) Preparation of starch gelatinized liquid: Disperse starch in water to make a suspension with a mass concentration of 1.0~8.0%, and then gelatinize the starch particles to break them and release short amylose to obtain starch gelatinized liquid; (3) Preparation of starch composite emulsion: Sucrose fatty acid ester is added to starch gelatinized liquid as emulsifier. The amount of sucrose fatty acid ester added is 0.5~3.0% of the mass of starch gelatinized liquid. Then vegetable oil is added. The mass ratio of vegetable oil to starch is 1:1~5:

1. Then homogenization is performed to make the vegetable oil evenly dispersed in starch gelatinized liquid to form a stable starch composite emulsion. (4) Pre-freezing blending: Sodium alginate solution and starch composite emulsion are mixed at a volume ratio of 1:1 to 3:1, stirred thoroughly and uniformly, and degassed to eliminate air bubbles introduced during the mixing process to obtain composite gel solution; (5) Pre-freezing and immobilization treatment: The composite gel solution is put into a mold and placed at -20~-80℃ for 2~12 hours to pre-freeze the gel system to form a stable frozen block structure; (6) Low-temperature slow crosslinking: Demold the pre-frozen frozen block and soak it in a low-temperature calcium chloride solution at 0~4℃ with a mass concentration of 1.0~10.0%; carry out a slow crosslinking reaction at low temperature for 12~48 hours to allow calcium ions to penetrate evenly and fully coordinate with the sodium alginate G block; after the crosslinking is completed, take out the gel and rinse the surface with deionized water. (7) Emulsion gel formation: The cross-linked gel is taken out and thawed to obtain a high gel strength sodium alginate-starch composite emulsion gel.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass concentration of sodium alginate solution is 1.0~4.0%; let the solution stand for 12~24 hours to ensure that the sodium alginate is fully hydrated and dissolved and to eliminate air bubbles in the solution, and then set it aside.

3. The preparation method according to claim 1, characterized in that: The starch in step (1) is one or more of corn starch, potato starch, cassava starch, wheat starch, pea starch, rice starch and their food-grade modified starches.

4. The preparation method according to claim 1, characterized in that: Step (2) gelatinization is microwave treatment. The specific steps are to place the suspension in a microwave device, set the microwave power to 400~800 W, the radiation heating time to 30~90 seconds, and let it cool naturally to room temperature to obtain a uniform starch gelatinized liquid.

5. The preparation method according to claim 1, characterized in that: The homogenization method in step (3) is to use a high-speed homogenizer for homogenization, with a homogenization speed of 8000~15000 rpm and a homogenization time of 3~10 minutes.

6. The preparation method according to claim 1, characterized in that: The vegetable oil mentioned in step (3) includes, but is not limited to, one or more of soybean oil, rapeseed oil, peanut oil, sunflower oil, and corn oil.

7. The high-strength sodium alginate-starch composite emulsion gel obtained by any one of the preparation methods according to claims 1-6, characterized in that: Size and shape are controllable, and hardness is 800~1000g.

8. The application of the high-strength sodium alginate-starch composite emulsion gel according to claim 7 as an animal fat substitute in processed foods.

Citation Information

Patent Citations

  • Preparation method of sodium alginate gel sustained-release pig back fat substitute and application of substitute to fermented sausages

    CN109601873A

  • Preparation of fat substitution and its application in meatballs

    CN109619537A